Isolation of the centromere-linked CDC10 gene by complementation in yeast. - Clarke, L (1980)
A hybrid plasmid colony bank was constructed in Escherichia coli using the E. coli-Saccharomyces cerevisiae shuttle vector pLC544 and randomly sheared segments of yeast DNA. By transformation with a hybrid plasmid DNA pool from this collection and complementation of a temperature-sensitive cdc10 mutation in yeast, a plasmid was isolated that carries 8 kilobase pairs of DNA around the chromosome III centromere-linked CDC10 locus. This DNA segment overlaps a larger region of DNA (40 kilobase pairs) previously identified to be around the LEU2 locus on chromosome III [Chinault, A.C. & Carbon, J. (1979) Gene 5, 111-126] and physically establishes the directionality of the cloned DNA sequences with respect to the genetic map and the centromere. In the leu2-cdc10 interval, the relationship between physical distance on the DNA and genetic distance as measured by recombinational frequencies is about 3 kilobase pairs per centimorgan.